A Bibliometric Analysis of Data Science: Trends, Contributions, and Research Developments - Muhamad Juliardi; Ibnu Malik (West Science Interdisciplinary Studies, 2023)
This research paper presents an analysis of the collected articles using the Publish or Perish software, consisting of the top 290 scientific articles listed on Google Scholar from 1947 to 2023. The study aims to explore the current state of the data science field in relation to technological advancements and the prevalence of big data. The findings reveal a significant and rapid development in the field, highlighting the importance of topics such as data science, big data, data analysis, and machine learning for further investigation.